Evaluation of tomato fruit quality response to water and nitrogen management under alternate partial root-zone irrigation - Hui, Yang; Hongxia, Cao; Xinmei, Hao; Lijie, Guo; Hongzheng, Li; Xuanyi, Wu (International Journal of Agricultural and Biological Engineering, 2017)
A pot experiment was conducted to investigate the effects of different water and nitrogen supply amounts on the comprehensive assessment of tomato fruit quality and root growth parameters under alternate partial root-zone irrigation. Three upper irrigation limitations (i.e. 70% (W1), 80% (W2) and 90% (W3) of field capacity, respectively) and three N-fertilizer levels (i.e. 0.18 (N1), 0.30 (N2) and 0.42 (N3) g/kg soil, respectively) were arranged with a randomized complete block design, and alternate partial root-zone irrigation method was applied. Results showed that fruit yields under deficit irrigation (W1 and W2) were decreased by 6.9% and 2.0% respectively compared with W3 under N1 level. Yields of tomato under W1N1 and W1N2 combinations were also reduced by 10.3% and 7.2%, respectively compared with W1N3 combination. Root dry weight, root length, root surface area and root volume were all increased in W1N2 treatment. According to two-way ANOVA, the root parameters except root dry weight, were extremely sensitive to water, nitrogen and the cross effect of the two factors. TSS (total soluble solids), SS (soluble sugars) and OA (organic acid) in the fruits increased with the decrease in irrigation water, OA and NC reduced with decreasing amount of nitrogen. Moreover, within an appropriate range, as more irrigation water and nitrogen were applied, the higher VC (vitamin C) and lycopene contents were identified in the fruits. Eventually, the combinational evaluation method (i.e. entropy method and gray relational analysis) showed that W2N2 ranked highest in comprehensive fruit quality. Therefore, considering the tradeoff between fruit comprehensive quality and yields, upper irrigation limitation of 80% θf and N-fertilizer of 0.30 g/kg soil with alternate partial root-zone irrigation was the optimal cultivation strategy for the greenhouse tomato in autumn-winter season in northwest China. Keywords: greenhouse tomato, alternate partial root-zone irrigation, water and nitrogen, root growth, comprehensive fruit quality DOI: 10.25165/j.ijabe.20171005.2622 Citation: Yang H, Cao H X, Hao X M, Guo L J, Li H Z, Wu X Y. Evaluation of tomato fruit quality response to water and nitrogen management under alternate partial root-zone irrigation. Int J Agric & Biol Eng, 2017; 10(5): 85–94.